The Mappasiala Tradition: Gateway to Underage Marriage in the Bugis Community of Southeast Sulawesi - Akbar, Muhammad; Adhim, Zakiyuddin Abdul; Kamaruddin, Kamaruddin; Darlis, Syamsul; Rachmadani, Rachmadani (SHAHIH: Journal of Islamicate Multidisciplinary, 2024)
Matchmaking traditions in Indonesia are always interesting to research, especially matchmaking to someone who is still underage, of course, this tradition raises social problems which, if confronted with the law, will generate debate. For example, the mamppasiala tradition often ignores the rights of prospective male and female brides in the practice of underage marriage. This research aims to reveal the practices, implications, and perspectives of maqasid syari'ah regarding the mappasiala tradition in underage marriage among the Bugis community of Southeast Sulawesi. This research is qualitative research with an empirical-normative approach which includes interviews with traditional actors, traditional leaders, community leaders, and religious leaders. The research results reveal that the practice of the mappasiala tradition goes through three stages; mappasiruntu pattujung, mappasicelleng, and mappakado wija. The mappasiala tradition has double implications (positive and negative) for underage marriage. Maqasid syari'ah views that the mappasiala tradition tends not to achieve the goals of marriage specifically and the goals of Islamic law in general. Therefore, ijtihad regarding the law on matchmaking and underage marriage is very necessary to meet the legal needs of contemporary society. Thus, it is hoped that this research can make a global contribution to developing the study of traditions, customs, and culture.